2007
DOI: 10.2307/30032491
|View full text |Cite
|
Sign up to set email alerts
|

Contraception with Levonorgestrel Subdermal Implants ($Norplant^R$) in Benin-City, Nigeria: A 12-year Review

Abstract: The case notes of 377 clients who accepted Norplant out of 11961 acceptors of family planning methods in the Department of Obstetrics and Gynaecology University of Benin Teaching Hospital, between January 1985 and December 1996 were retrieved and analysed at the end of 2004, for socio-demographic characteristics of the clients, side effects and complications reported and reasons for discontinuation in relation to duration of use. The daily register of the acceptors were analysed for new acceptors of other meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(38 reference statements)
0
5
1
1
Order By: Relevance
“…Previous studies have suggested a small incidence of decreased sexual desire (<2.0%) in users of an LNG-SI (21,22). We were unable to find any evidence of changes in sexual function.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have suggested a small incidence of decreased sexual desire (<2.0%) in users of an LNG-SI (21,22). We were unable to find any evidence of changes in sexual function.…”
Section: Discussioncontrasting
confidence: 76%
“…Combination oral contraceptives and LNG SC implants (LNG-SI) have been shown to decrease sexual desire in a small percentage of women (21)(22)(23). One of the difficulties with this assessment is that desire is more subjective than objective.…”
mentioning
confidence: 98%
“…Further, no data on continuation of contraceptive use were collected beyond nine months postpartum. However, studies from other countries indicate that continuation rate for hormonal implants are high [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 92%
“…41 Other studies on Norplant acceptability, effectiveness, common side effects, and reasons for discontinuation among Nigerian women have been carried out in Benin city, 42 Zaria, 43 and Calabar. 44 These studies showed a promising future for implant contraceptives in Nigeria, particularly in the Hausa and Muslim communities of northern Nigeria where contraceptive use has been generally low.…”
Section: Hormonal Contraceptive Injection/implantmentioning
confidence: 99%